A service provider perspective in Irish horseracing on the availability of retirement specific support services for professional jockeys and perceived barriers and facilitators to their use - Laura Langton; Sarah Jane Cullen; Giles Warrington; Jennifer Pugh; Adrian McGoldrick; Ciara Losty (PLoS ONE, 2026)
Retirement can come at any time in horse racing due to the unpredictable nature of the sport. Preplanning for the retirement transition in sport has been reported to lead to faster adjustment to retirement and better transition for athletes. The purpose of this study was to highlight the current support services available to Irish horseracing jockeys to aid with career transitions and to a) explore perceived barriers and b) perceived facilitators to their use. Semi-structured interviews were conducted with 11 representatives from various racing bodies including the Irish Horse Racing Regulatory Board (IHRB), Horse Racing Ireland (HRI), Racing Academy Centre of Education (RACE), Irish Jockeys Trust (IJT), The Jockeys Association (JA), Injured Jockeys Fund (IJF), Equipp and The Jockeys Pathway. Questions included, demographic information, perceptions of current use of support services, perceptions of barriers preventing jockeys from using support services and perceived facilitators to the use of support services in the future. Reflexive thematic analysis was used to analyse qualitative data that included inductive and deductive approaches. The higher order themes identified as barriers to use of transition support services, were the culture within the Irish horseracing industry, and insufficient cross organisation communication. Higher order themes relating to facilitators of engagement were accessible further education opportunities for jockeys, normalising career planning and the development of an exemplar support service for jockey career transitions. Normalising career planning and implementing an exemplar support programme for retiring jockeys is vital to ensure jockey wellbeing needs are met as they transition at the end of their racing career.